Internal Security Threat to India from State Sponsored Terrorism by Pakistan: Exploring the Implications of State-sponsored Terrorism in Kashmir (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The study of various politico-security implications of terrorism in Pakistan and state-sponsored terrorism for India becomes imperative in the presence of deteriorating security situation in the country especially in context of Kashmir. The paper throws light on the deteriorating security situation in India due to state-sponsored terrorism by Pakistan especially in context of Kashmir and brings out various politico-security implications of terrorism in Pakistan for India. The chapter also draws our attention to the issue of state terrorism as one of the important implications and the human rights violation by the state institutions that have taken place under the aegis of legislative rules such as Armed Forces Special Protection Act (AFSPA).